Florida's Wading Birds - Grant C. Sizemore; Martin B. Main; Elise V. Pearlstine (EDIS)
WEC-264, an 11-page illustrated fact sheet by Grant C. Sizemore, Martin B. Main, and Elise V. Pearlstine, provides an overview of some of the most majestic of Florida's birds — taxonomy and status, cranes and flamingos, identification, feeding behavior, diet, breeding, movements, and conservation. Includes references. Published by the UF Department of Wildlife Ecology and Conservation, July 2009.